YWHAG Mutations Cause Childhood Myoclonic Epilepsy and Febrile Seizures: Molecular Sub-regional Effect and Mechanism - Ye, Xing-Guang; Liu, Zhi-Gang; Wang, Jie; Dai, Jie-Min; Qiao, Pei-Xiu; Gao, Ping-Ming; Liao, Wei-Ping (Frontiers in Genetics, 2021)
YWHAG, which encodes an adapter protein 14-3-3γ, is highly expressed in the brain and regulates a diverse range of cell signaling pathways. Previously, eight YWHAG mutations have been identified in patients with epileptic encephalopathy (EE). In this study, using trios-based whole exome sequencing, we identified two novel YWHAG mutations in two unrelated families with childhood myoclonic epilepsy and/or febrile seizures (FS). The identified mutations included a heterozygous truncating mutation (c.124C>T/p.Arg42Ter) and a de novo missense mutation (c.373A>G/p.Lys125Glu). The two probands experienced daily myoclonic seizures that were recorded with ictal generalized polyspike-slow waves, but became seizure-free with simple valproate treatment. The other affected individuals presented FS. The truncating mutation was identified in the family with six individuals of mild phenotype, suggesting that YWHAG mutations of haploinsufficiency are relatively less pathogenic. Analysis on all missense mutations showed that nine mutations were located within 14-3-3γ binding groove and another mutation was located at residues critical for dimerization, indicating a molecular sub-regional effect. Mutation Arg132Cys, which was identified recurrently in five patients with EE, would have the strongest influence on binding affinity. 14-3-3γ dimers supports target proteins activity. Thus, a heterozygous missense mutation would lead to majority dimers being mutants; whereas a heterozygous truncating mutation would lead to only decreasing the number of wild-type dimer, being one of the explanations for phenotypical variation. This study suggests that YWHAG is potentially a candidate pathogenic gene of childhood myoclonic epilepsy and FS. The spectrum of epilepsy caused by YWHAG mutations potentially range from mild myoclonic epilepsy and FS to severe EE.